A comparison of intranasal dexmedetomidine for sedation in children administered either by atomiser or by drops. (3rd March 2016) - Li, B. L.; Zhang, N.; Huang, J. X.; Qiu, Q. Q.; Tian, H.; Ni, J.; Song, X. R.; Yuen, V. M.; Irwin, M. G.
Summary: Intranasal dexmedetomidine has been used successfully for sedation in children. A mucosal atomisation device delivers an atomised solution to the nasal mucosa which facilitates rapid and effective delivery of medication to the systemic circulation. We compared intranasal delivery of dexmedetomidine in a dose of 3 μg.kg −1 by either atomiser or drops from a syringe in children < 3 years old undergoing transthoracic echocardiography. Two hundred and seventy‐nine children were randomly assigned to one or other group. One hundred and thirty‐seven children received dexmedetomidine by atomiser and 142 by drops. The successful sedation rate was 82.5% (95% CI 75.3–87.9%) and 84.5% (95% CI 77.7–89.5%) for atomiser and drops, respectively (p = 0.569). Sedation tended to be less successful in older children (p = 0.028, OR 0.949, 95% CI 0.916–0.983). There were no significant complications. We conclude that both modes of dexmedetomidine administration are equally effective, although increasing age of the child was associated with a decreased likelihood of successful sedation.